2019
DOI: 10.1038/s41598-018-37761-7
|View full text |Cite
|
Sign up to set email alerts
|

Telencephalon transcriptome analysis of chronically stressed adult zebrafish

Abstract: Chronic stress leads to disruptions in learning and memory processes. The effects of chronic stress experience on the adult zebrafish brain, particularly the memory associated telencephalon brain region, is unclear. The goal of this study was to identify gene expression changes in the adult zebrafish brain triggered by chronic unpredictable stress. Transcriptome analysis of the telencephalon revealed 155 differentially expressed genes. Of these genes, some are critical genes involved in learning and memory, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…S4, and S5). Similarly to previous studies, we also found changes in the expression of interferon inducible proteins IFI6/IFI27-like associated genes and pathways 69 ( Supplementary Fig. S5).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…S4, and S5). Similarly to previous studies, we also found changes in the expression of interferon inducible proteins IFI6/IFI27-like associated genes and pathways 69 ( Supplementary Fig. S5).…”
Section: Discussionsupporting
confidence: 89%
“…2, Tables 2, 3). However, some other reports failed to evoke overt anxiety 69 , raising questions of whether CUS protocol was indeed properly applied in such studies (e.g., see 70,71 for a recent discussion of challenges with data reliability and replicability in zebrafish behavioral models). Thus, further research is needed, for example, to compare zebrafish that received CUS protocols that would differ in the numbers of stressors, their severity and/or duration.…”
Section: Discussionmentioning
confidence: 99%
“…Given our hypothesis that the enteric neurons further along a differentiation program were localized to the distal tip of Sub-Cluster 3, we asked whether this population of cells contained additional neurochemical or neuron subtype specific differentiation genes. As expected, a small pocket of these cells was found to contain the two acetylcholine associated genes, acetylcholine esterase (ache) (Bertrand et al, 2001;Huang et al, 2019) and vesicular acetylcholine transferase (slc18a3a) (Hong et al, 2013;Zoli, 2000) (Furness et al, 2004;Memic et al, 2018). Corroborating our single-cell findings, HCR analysis revealed the co-expression of pbx3b, calb2a, vipb, nos1, and slc18a3a in discrete differentiating enteric neurons within the foregut region of the zebrafish gut at 68 hpf ( Figure 5G).…”
Section: Sox10-derived Cells During the Embryonic To Early Larval Trasupporting
confidence: 84%
“…Scientific RepoRtS | (2019) 9:17063 | https://doi.org/10.1038/s41598-019-53634-z www.nature.com/scientificreports www.nature.com/scientificreports/ changes in the HF diet-fed zebrafish. Recently, Huang et al34 performed RNA sequencing analysis of the telencephalon in chronically stressed adult zebrafish and revealed the altered expression of 155 genes, some of which are known to be critical for memory. Although this chronic stress treatment did not include dietary stress, we consider that the HF diet might also produce memory-associated gene expression changes in the telencephalon of zebrafish similar to that in mammals[28][29][30][31][35][36][37] .…”
mentioning
confidence: 99%